Implementation of the ISO 9001 quality management system - process, impact and benefits - Drenovac, Aleksandar Ž.; Drenovac, Bratislav Ž.; Drenovac, Dušan M. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Modern business is characterized by greater and greater market competition through all business areas and all activities. Establishment of market positions is a very important element of business activities in every organization. Quality of products and/or services provides recognizability at market and raising of ratings. Implementation of the ISO 9001 quality management system opens positions for secure national and international markets; it is also an identifier of an efficiently and effectively process-wise organized system in an organization. Introduction An increase of impact of quality and demands for ensuring quality before contract approvals has been visible lately. All vendors at the multinational market must ensure confidence in the quality of their products or services in order to satisfy customer demands which is an ultimate goal. Organizations which have the certificated ISO 9001 standard are known for their persistence and reliability, so they reach high reputation by applying  the standard. Implementation of a quality management system Implementation of a quality management system is done by system engineering, as a process based on a top management decision. It can be applied through the engagement of professionals from within the organization, as well as through outsourced consultants. The process is based on the PDCA cycle and the eight principles of quality management in an ISO 9001 organization. Defining assignments in accordance with the standard The Quality Manual, as a document which contains quality aims and through which a complete model of the quality management system is described, should be an initial element for the process of implementing a quality management system. It contains an overview of all procedures and directions used for achieving quality policy, i.e. for the implementation of a quality management system in every part of a business system. Implementation of procedures When the Quality manual is created, it is necessary to identify necessary procedures, in order to ensure fulfillment of all requirements. The aim is to establish an optimal system using as few procedures as posible. Therefore, it is necessary to choose first few procedures very carefully and implement them so that emloyees gain confidence. Procedures must be defined in such a way that they determine activities and responsibilities for particular jobs. Drawing up instructions and records Work instructions are documents that describe a way of accomplishing activities defined by procedures. Based on them, every competent executor would be able to complete a determined job. Records are documents that give objective evidence that a quality management system entirely conforms with standard requirements. As opposed to procedures, they are unchangeable and they record what was done, who did what, how something was done, and what was achieved. Implementation and control of a quality management system Implementing a quality management system opens a new process of system monitoring, reevalutation and improvement, thus entering first into a process of internal auditing. Internal audits have a purpose of marking positions at which the process in unsuccessful, of detecting deviations and improving the system. Certification Positive experience shows that a certification institution should be chosen at least three months before a formal evaluation is planned. Also, it is very important to choose a certification institution which is accepted, recognized and entirely accredited (BSI, LRQA, TÜV SUD, SGS, Bureau Veritas, etc.). Ther is no certification body that has total accreditation, but only accredited fields in which they can demonstrate relevant experience. Impact and benefits of the establishment of ISO 9001 system Entering the process of certification indicates commitment to quality, which reflects in lower costs due to fewer nonconformed products, lfewer refused products as well as in fewer faults in general. Relation between military and ISO standards ISO standards themselves were derived from military standards, so it became necessary to achieve particular standards in order to deliver equipment and parts to military organizations. Many countries in their military standards directly refer to the requirements of ISO 9001 standards, so the implementation of a quality management system gives possibilities to access global military industry markets. Conclusion: Standardization represents a very important activity for all business processes as well as for establishing the criteria according to which the evaluation of processes and organizations will be performed. Implementation of the ISO 9001 quality management system represents the proof that the organization set effectively the processes that ensure effectivity of the whole system, thus opening a possibility of engagement at different markets and increasing the rating at the same time. Also, implementation of the ISO 9001 quality management system considers meeting system requirements. In order to establish an efficient system, it is necessary to engage professional consultants, which ensures recognizability and acknowledgment of quality for engagement at different markets. Implementation of the ISO 9001 quality management system opens a possibility to enter different markets of military industry worldwide.
Keywords: quality; management systems; Quality management; ISO